2004
DOI: 10.1103/physreva.70.012107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Casimir-Polder energy between an excited- and a ground-state atom

Abstract: We consider the Casimir-Polder interaction between two atoms, one in the ground state and the other in its excited state. The interaction is time dependent for this system, because of the dynamical self-dressing and the spontaneous decay of the excited atom. We calculate the dynamical Casimir-Polder potential between the two\ud atoms using an effective Hamiltonian approach. The results obtained and their physical meaning are discussed and compared with previous results based on a time-independent approach, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 16 publications
5
78
0
Order By: Relevance
“…By an appropriate time-averaging procedure [18] or in the limit of vanishing atomic line widths [19], a third result, for the vdW interaction on the excited atom, was found that oscillates in magnitude and sign. Note that an earlier approach based on time-dependent perturbation theory yields a non-oscillatory result for the force on the ground-state atom that is however valid only for times shorter than the lifetime of the excited state [20]. Similar considerations about timescales hold for the diagrammatic nonequilibrium description used in Ref.…”
Section: Arxiv:150300986v2 [Quant-ph] 23 Feb 2017mentioning
confidence: 76%
“…By an appropriate time-averaging procedure [18] or in the limit of vanishing atomic line widths [19], a third result, for the vdW interaction on the excited atom, was found that oscillates in magnitude and sign. Note that an earlier approach based on time-dependent perturbation theory yields a non-oscillatory result for the force on the ground-state atom that is however valid only for times shorter than the lifetime of the excited state [20]. Similar considerations about timescales hold for the diagrammatic nonequilibrium description used in Ref.…”
Section: Arxiv:150300986v2 [Quant-ph] 23 Feb 2017mentioning
confidence: 76%
“…In this coupling scheme the momentum conjugate to the vector potential is the transverse displacement field, which outside the atoms coincides with the electric field (transverse plus longitudinal) [14]. We evaluate the three-body CP interaction energy from the interaction of one atom with the time-dependent field emitted by the two other atoms; this is a generalization of a method already used in a time-independent situation for three atoms [9] and also in time-dependent cases for the two-body potential [15]. Only terms involving coordinates and polarizabilities of all atoms are relevant for the three-body potential.…”
mentioning
confidence: 99%
“…For previous work in this field, see e.g., [19][20][21][22]. Since we are here working with the UdW model, we can go beyond the usual proximity field approximation.…”
Section: Arxiv:13117619v2 [Quant-ph] 21 Mar 2014mentioning
confidence: 99%
“…One small caveat is that this simple model encodes the basic features of the light-matter interaction for atomic transitions only in the absence of the exchange of orbital angular momentum [18]. The model has been used in studies of Casimir-Polder forces involving only one conducting plate [19][20][21][22] and is commonly used in studies of quantum field theory in curved spacetimes and relativistic quantum information [30][31][32][33][34][35], as well as in quantum optics (see, e.g., [36]). However, the model does not contain the analog of a diamagnetic field self-interaction term as in (1).…”
Section: Field-matter Interaction Modelsmentioning
confidence: 99%
See 1 more Smart Citation